Development of Patient Experience Questionnaire for Virtual Consultation Services in the Primary Healthcare: Content and Face Validty Analysis - Nasim Abdul Kuthoose; Mohamad Rodi Isa; Khalid Ibrahim (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background: Patient experience measures objective aspects of healthcare and correlates with improved patient outcomes. Existing standardized questionnaires, including Malaysia's Client Experience Survey, focus on physical consultations. The COVID-19 pandemic accelerated the adoption of virtual consultations in Malaysia. However, validated tools to assess patient experiences with virtual primary care tailored to Malaysia's local context remain lacking. Objective: This research aims to develop a patient experience questionnaire for virtual primary care consultations in Malaysia and establish its content and face validity. Research Methods/Implementation Methods: Items were developed from a framework based on literature reviews and refined through expert panels. To assess validity, nine field experts and ten experienced patients participated in the study. The content validity index (CVI), content validity ratio (CVR), and face validity index (FVI) were evaluated. Results: The initially developed items consisted of 55 items aligned with the Picker Principle – TAMs’ domains. After receiving expert feedback, the instrument was refined to 47 items across seven domains. A Delphi panel's content evaluation retained 35 items, discarding 8 with a relevance I-CVI of ≤ 0.78 and refining 12 statements. Face validity testing with 10 adult participants highlighted seven items with poor ratings and 11 borderline items. Based on this feedback, eight items were revised and eight were removed due to low I-FVI, resulting in a total of 39 items. Conclusion/Lesson Learned : Findings on content and face validity highlight the need to include infrastructure and essential service elements when assessing patient experience in virtual primary care consultations. This framework guides providers to enhance patient experience. Further psychometric and reliability testing with larger samples is needed to verify construct validity and reliability over time.